2019
DOI: 10.18203/2320-6012.ijrms20190921
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cholecystitis with follicular lymphoid hyperplasia: nomenclature and diagnostic dilemmas

Abstract: Background: To revisit the nomenclature, prevalence, histogenesis and the diagnostic dilemmas in cases of cholecystitis with lymphoid hyperplasia received in a private laboratory in one-year duration.Methods: A total of 51 cases of cholecystectomy were examined histopathologically to identify and review all the cases with emphasis on cholecystitis with marked lymphoid infiltration.Results: Out of 51 cholecystectomy specimens, some rare entities were observed such as 4 cases (8%) of xanthomatous change, 2 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…7,8 For the diagnosis, an increase in the number of intraepithelial lymphocytes per 100 biliary cells above the normal proportion of three to four lymphocytes is needed. 9 The pathogenesis of CFC is unclear although it may be caused by an immune reaction to luminal agents of the gallbladder. 10 Other theories include an autoimmune-mediated disorder in other areas of the gastrointestinal tract or gram-negative bacterial infection that induce a lymphocytic reaction, such as E. coli, K. pneumoniae, or S. typhi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 For the diagnosis, an increase in the number of intraepithelial lymphocytes per 100 biliary cells above the normal proportion of three to four lymphocytes is needed. 9 The pathogenesis of CFC is unclear although it may be caused by an immune reaction to luminal agents of the gallbladder. 10 Other theories include an autoimmune-mediated disorder in other areas of the gastrointestinal tract or gram-negative bacterial infection that induce a lymphocytic reaction, such as E. coli, K. pneumoniae, or S. typhi.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other theories include an autoimmune-mediated disorder in other areas of the gastrointestinal tract or gram-negative bacterial infection that induce a lymphocytic reaction, such as E. coli, K. pneumoniae, or S. typhi. [9][10][11] This inflammatory pattern can be encountered in other parts of the gastrointestinal tract such as the esophagus, stomach, duodenum and colon, and in the orbits and lungs. 8 Risk factors for developing CFC are unclear because there are uncertain causal associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On reviewing Indian literature on FC, we observed that, there are very few case reports of FC. [2][3][4]8 Mohan et al 9 studied 1100 cholecytectomies in North india and reported a high incidence of 2.3% with 26 cases of FC. Mahajan et al 6 studied 656 cases of cholecystectomies and reported relatively low incidence of 0.61% (4 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, Escherichia coli, Klebsiella pneumoniae, and Salmonella typhi infections caused by gram-negative bacteria have been linked to follicular cholecystitis [5,6]. In addition, many chronic cholecystitis patients exhibit pyloric metaplasia and detectable Helicobacter pylori infection of the gallbladder mucosa, albeit this does not seem to predict the particular histologic subtype [7,8].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%